SIMBOLISASI DAN IKONISASI: METODE ALTERNATIF MEMAHAMI ARABIC TERMS PADA PRODUK PERBANKAN SYARIAH (Equilibrium: Jurnal Ekonomi Syariah, 2017)
Nowdays, the growth of Islamic banking have some obstacles such as a weakness of product innovation and product knowledge. Because many Islamic banking product used name of Arabic terms.  Both of which are very important be concerned to build up the competitiveness of Islamic banking in Indonesia. This study aims to provide an alternative method to make simplify the understanding of the Arabic terms on Islamic banking products using the symbols and icons to keep it simple and easily understood by the public (customers). The type of research that used in this study was library research category. The results of a literature review find that the urgency of product innovation by the Islamic banking stakeholder has been ideally matched with product knowledge, which were always labeled with Arabic terms. Symbolization could be an alternative method to facilitate the customer understanding on Arabic terms in Islamic banking products